(a + b) / 2 = 40
a + b = 40 x 2
a + b = 80
therefore c = 20
(b + c) / 2 = 35
b + c = 35 x 2
b + c = 70
therefore a = 30
a + b + c = 100
30 + b + 20 = 100
b = 100 - 30 - 20
b = 50
a = 30
b = 50
c = 20
2007-01-14 08:33:41
·
answer #1
·
answered by Anonymous
·
2⤊
1⤋
Mean (A + B) = 40 = (A + B)/2
80 = A + B
Similarly (B + C) = 35 = (B + C)/2
70 = B + C
Using Simultaneous Equations
A + B = 80
B + C = 70 (x -1)
A + B + C = 100
A + B = 80
- B - C = -70
A + B + C = 100
2A + B = 110
A + B = 80 ( x -1)
2A + B = 110
-A - B = -80
A = 30
Substituting in :-
A + B = 80
30 + B = 80
B = 80 - 30 = 50
Substituting in again :-
A + B + C = 100
30 + 50 + C = 100
C = 100 - 30 -50 = 20
A = 30
B = 50
C = 20
2007-01-14 16:45:15
·
answer #2
·
answered by lenpol7 7
·
0⤊
0⤋
1. (A + B) /2 = 40 thus A + B = 80
2. (B + C) /2 = 35 thus B + C = 70
3. A + B + C =100
from 3, 80 + C = 100 so C = 20
from 2, B + C = 70 so B = 50
from 1, A + B = 80 so A = 30
2007-01-14 16:49:00
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
if the mean of A &B is 40, then (A +B)/2=40 or A + B =80 ....(1); equally (B + C)/2 = 35 or B +C =70....(2)
from ...(1) A = 80 - B and from ...(2) C =70 - B
A + B + C =100 ....(3)
substitute A & C for B in ...(3)
thus: (80 - B ) + B + (70 - B)= 100; -B + 150 = 100; - B = -50
B= 50 therefore, A = 80 - 50 = 30, C =70 - 50 = 20
B is 50, A is 30, C is 20
2007-01-15 16:17:28
·
answer #4
·
answered by Reginald N 1
·
0⤊
0⤋
(a+b)/2=40 cross multiply becomes a+b=80
(b+c)/2=35 cross multiply becomes b+c=70
A+B+C=100
a+b=80
b+c=70 can be written as b = 70-c as well
since b is a constant, a = c+10 (let b = 0 in both equations -- then a=80 and b=70 ... let b = 10 .... a=70, b= 60 ..... a is always 10 more than c
a=c+10
substitute c+10 for a in the last equation
substitue
a+b+c=100
c+10+b+c=100
2c+10+b=100
2c+b=90
as writen above, since b+c=70, b= 70-c --- so we can substitute again
2c+70-c=90
c+70=90
c=20
now substitute into the originals
b+c=70
b+20=70
b=50
a+b=80
a+50=80
a=30
so the answers are
a=30
b=50
c=20
2007-01-14 16:43:30
·
answer #5
·
answered by Bill F 6
·
0⤊
0⤋
A + B=80-----------1
B + C=70-----------2
A + B + C = 100---3
Rearrange 1 to make A= 80 -B and substitute into 3 this gives
80 - B + B + C=100
80 + C=100
C=20
Substitute C=20 into 2 to give
B + 20 = 70
B=50
Substitute B= 50 and C=20 into 3 to give
A + 50 + 20 = 100
A + 70 = 100
A= 30
In summary
A=30
B=50
C=20
2007-01-14 16:38:05
·
answer #6
·
answered by missree 5
·
1⤊
0⤋
(a+b)/2=40
(b+c)/2=35
a+b+c=100
solve for a and c from the first and second equation.
a+b=80
a= 80-b
b+c=70
c= 70-b
sub a and c for the 3rd equation.
80-b+b+70-b=100
-b+150=100
b= 50
a=80-b
a=80-(50)
a=30
c=70-b
c=70-(50)
c=20
2007-01-14 16:44:09
·
answer #7
·
answered by 7
·
0⤊
0⤋
(a+b)/2=40 so a+b=80
a+b+c=100 ---> 80+c=100 which means c is 20
(b+c)/2=35 so b+c=70 and c is 20 so minus that and you get b is 50 which means a is 30
a=30, b=50, c=20
2007-01-14 16:41:24
·
answer #8
·
answered by 123 4
·
0⤊
0⤋
ok this was a tough one so here's the answer. If the mean of a+b=40 then a+b=80, mean of b+c=35 then b+c=70 b/c mean is the average number, there is 2 numbers the equation for mean is (a+b)/2=40. same concept for the mean of b+c=35. anyways heres the answer if you have any other questions about how i i got the answer just email me at qikfeet_89@yahoo.com...her;s the answer A=30, B=50, C=20
2007-01-14 16:59:49
·
answer #9
·
answered by Danny 1
·
0⤊
0⤋
(A+B)/2 = 40 (from the definition of mean)
(B+C)/2 = 35 (again, from the definition of mean)
A+B+C = 100 (given in problem)
Since (A+B)/2 = 40 that means A + B = 80
A+B+C = 100, so
(A+B) + C = 100
80 + C = 100
C = 20
Now, since (B+C)/2 = 35 that means B+C = 70
Replace C with 20
B + 20 = 70
B = 50
From above, A + B = 80, then replace B with 50
A + 50 = 80
A = 30
Answer: A = 30, B = 50 and C = 20
2007-01-14 16:34:10
·
answer #10
·
answered by MsMath 7
·
3⤊
1⤋